New Developments in Biomarkers for Atopic Dermatitis - Thijs, Judith L.; Seggelen, Wouter van; Bruijnzeel-Koomen, Carla; Bruin-Weller, Marjolein de; Hijnen, DirkJan (My University, 2015)
The application of biomarkers in medicine is evolving. Biomarkers do not only give us a better understanding of pathogenesis, but also increase treatment efficacy and safety, further enabling more precise clinical care. This paper focuses on the current use of biomarkers in atopic dermatitis, new developments and future perspectives. Biomarkers can be used for many different purposes, including the objective determination of disease severity, confirmation of clinical diagnosis, and to predict response to treatment. In atopic dermatitis, many biomarkers have been investigated as a marker for disease severity. Currently serum thymus and activation-regulated chemokine (TARC) is the superior biomarker for assessing disease severity. However, we have recently shown that the use of a panel of serum biomarkers is more suitable for assessing disease severity than an individual biomarker. In this overview, we will discuss alternative sources for biomarkers, such as saliva and capillary blood, which can increase the user friendliness of biomarkers in atopic dermatitis (AD). Both methods offer simple, non-invasive and cost effective alternatives to venous blood. This provides great translational and clinical potential. Biomarkers will play an increasingly important role in AD research and personalized medicine. The use of biomarkers will enhance the efficacy of AD treatment by facilitating the individualization of therapy targeting the patients’ specific biological signature and also by providing tools for predicting and monitoring of therapeutic response.
Keywords: atopic dermatitis; eczema; biomarkers; disease severity; stratification; dried blood spots; saliva